Feeding ecology of Rivulus luelingi (Aplocheiloidei: Rivulidae) in a Coastal Atlantic Rainforest stream, southern Brazil - Abilhoa,Vinícius (2010)
Feeding habits of the killifish Rivulus luelingi collected in a black water stream of the Coastal Atlantic Rainforest in southern Brazil were investigated. Eight samplings were made between April 2003 and January 2004. The diet, assessed through a similarity matrix with the estimated contribution values of food items, included microcrustaceans, aquatic immature insects (larvae and pupae), aquatic adult insects, terrestrial insects, insect fragments, spiders, and plant fragments. Differences in the diet according to temporal variations (months) were registered, but changes related with size classes evaluated and high/low precipitation period were not observed. The species presented an insectivorous feeding habit, and its diet in the studied stream was composed of autochthonous (mainly aquatic immature insects) and allochthonous (mainly insect fragments) material.